2021
DOI: 10.1508/cytologia.86.255
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Delay and Colchicine Like Metaphase Inducing Effects of <i>Scutellaria discolor</i> Colebr. Herb Aqueous Extract in <i>Allium cepa</i> Root Apical Meristem Cells

Abstract: Scutellaria discolor Colebr. (Family Lamiaceae, common name: bicolor skullcap) is a traditionally used medicinal plant. The present study aimed to analyze cell cycle delay and colchicine like metaphase (c-metaphase) inducing effects of aqueous extract of S. discolor herb (AESD) in onion, Allium cepa, root apical meristem cells. Onion root growth retardation, mitotic index, dividing cell frequencies, and c-metaphase frequency were analyzed after AESD treatment. The AESD induced a concentration-dependent onion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The microtubule destabilization induced by colchicine is reversible in nature and microtubule destabilization re-sults in an array of abnormalities in dividing cells (Levan 1938, Ray et al 2013. In our earlier study, we have reported the effect of AESD on root growth inhibition, delay in cell cycle due to increase in metaphase as well as c-metaphase cells frequency with a decrease in anaphase cells frequency in A. cepa and found a similar action with that of colchicine (Chakraborty et al 2021). The present study aimed to compare the AESD induced mitotic abnormalities with that of the colchicine in root meristematic cells of A. cepa.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The microtubule destabilization induced by colchicine is reversible in nature and microtubule destabilization re-sults in an array of abnormalities in dividing cells (Levan 1938, Ray et al 2013. In our earlier study, we have reported the effect of AESD on root growth inhibition, delay in cell cycle due to increase in metaphase as well as c-metaphase cells frequency with a decrease in anaphase cells frequency in A. cepa and found a similar action with that of colchicine (Chakraborty et al 2021). The present study aimed to compare the AESD induced mitotic abnormalities with that of the colchicine in root meristematic cells of A. cepa.…”
mentioning
confidence: 54%
“…1). Earlier we have reported that the most frequent abnormality induced by AESD is c-Metaphase (cM) (Chakraborty et al 2021). Owing to the persisting metaphase signal in cM condition, chromosomes get highly condensed producing sticky chromosomes (SC), and delay in metaphase to anaphase transition is observed (Ade andRai 2010, Chakraborty et al 2021).…”
Section: Resultsmentioning
confidence: 98%
“…The IC 50 value of LAEMM for RGR was found to be 0.204 mg mL 1 at 48 h. The IC 50 values for the RGR at 48 h are considered reliable for the evaluation of antiproliferative and cytotoxic effects of tested substances (Konuk et al 2007, Barman et al 2020. There are several previous reports available, which showed the antiproliferative and cytotoxic effects of the various plant extracts by analyzing the RGR effects and MAs (Murthy et al 2011, Ray et al 2013, Udo et al 2014, Kundu and Ray 2016, Barman et al 2020, Chakraborty et al 2021, Das et al 2021.…”
Section: Resultsmentioning
confidence: 98%
“…Colchicine is a mutagen causes polyploidy, or doubling of chromosome sets (Syaifudin et al, 2013). Colchicine arrests cells from dividing in the metaphase because colchicine ceases the formation of spindle threads (Chakraborty et al, 2021). Colchicine causes the plants become sturdier, plant parts are larger so that it may fix characteristics much better; beside Colchicine can change the composition of proteins, vitamins and carbohydrates (Syaifudin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%